Water constraints on the photoinduction of weed seed germination during tillage - Botto, Javier Francisco (2000)
Germination of light-requiring seeds may be induced by very brief exposure to sunlight during soil disturbance through the very-low fluence (VLF) mode of phytochrome action. We studied the effect of soil water availability after cultivation on the photoinduction of seed germination in two important weed species, Datura ferox andChenopodium album. In daily-irrigated plots, seedling density was 1- to 4-fold greater in plots cultivated during daytime than in those tilled at night. In contrast, when plots were not irrigated soon after tillage and rainfall was excluded, no significant differences were observed between seed germination in daytime vs night-time cultivated plots, although seedling emergence in night-time cultivated plots was higher than in non-cultivated controls. The average critical value of soil water potential required for the expression of VLF-induced germination was higher than –0.5 MPa (at 3-cm depth during the 6 d following cultivation). Dark germination was less sensitive to decreasing soil moisture than light-induced seed germination. The promotive effect of the light signal perceived by the seeds during daytime cultivation is maintained for several days (ca 6) in drying soil, even though laboratory data suggest that the far-red-light absorbing form of the phytochrome inducing the VLF photoresponse is unstable, disappearing in less than 24 h. These results reveal the complexity of interactions between the light signal and other environmental factors that control seed germination under natural conditions.